Diversity of Honeybee Behavior Is a Potential Inbuilt Trait for Varroa Tolerance: A Basic Tool for Breeding Varroa-Resistant Strains - Peter Njukang Akongte; Daegeun Oh; Changhoon Lee; Yongsoo Choi; Dongwon Kim (Agriculture, 2024)
The ectoparasitic mite Varroa destructor is well known for transmitting a number of viruses that can contribute to the collapse of honeybee colonies. To date, the many control measures put in place to limit the spread of V. destructor have yielded no satisfactory results. This is challenging because the effect of the parasite on honeybee colonies is becoming notorious. This has weakened the beekeeping industry and reduced pollination services, which may contribute to global food insecurity in the future. Therefore, it is necessary to put in place possible control measures and outline sustainable approaches to mitigate research efforts against the Varroa destructor. Extensive research to elaborate on the best possible solution has revealed that the selective breeding of naturally occurring V. destructor immune-related traits of honeybee strains is sustainable. Since the Integrated Pest Management approach was introduced, while still being very unreliable, there are open questions as to what control strategy could be considered effective. After cross-examination of existing strategies, a more practical way could be the adoption of an integrated approach. This approach should involve the association of selective breeding of honeybee colonies with V. destructor immune-related traits and the application of soft chemical treatment.